Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises - Page 277: 61



Work Step by Step

According to the negative exponent rule, $a^{-n}=\frac{1}{a^{n}}$. Therefore, $\frac{2^{-2}}{3^{-3}}=\frac{1}{\frac{2^{2}}{3^{3}}}=1\div\frac{2^{2}}{3^{3}}=1\times\frac{3^{3}}{2^{2}}=1\times\frac{27}{4}=\frac{27}{4}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.